2011
DOI: 10.1198/tech.2011.08157
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Annealing Model Search for Subset Selection in Screening Experiments

Abstract: The analysis of screening experiments based on nonregular designs can lead to a model selection problem in which the number of variables is large, the number of trials is small, and there are constraints on model structure. Common subset selection methods do not perform well in this setting. We propose a new approach particularly well suited to screening. The method uses an intentionally nonconvergent stochastic search to generate a large set of well-fitting models, each with the same number of variables. Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…For any individual simulated dataset, we would expect an expert user to outperform our analyses, for example, by using the graphical methods of Wolters and Bingham (2011) to better interpret the results from SAMS.…”
Section: Results From the Studymentioning
confidence: 98%
See 2 more Smart Citations
“…For any individual simulated dataset, we would expect an expert user to outperform our analyses, for example, by using the graphical methods of Wolters and Bingham (2011) to better interpret the results from SAMS.…”
Section: Results From the Studymentioning
confidence: 98%
“…Wolters and Bingham (2011) suggested an entropy criterion for selecting a single model but found that, in some cases, multiple models may have very similar entropy values. In this article, we select a final set of active effects by comparing the threshold t to the average absolute estimated coefficient for each effect; here, the average is computed across all models visited by the SA algorithm that were found to include the effect.…”
Section: Simulated Annealing Model Search (Sams) Wolters and Binghammentioning
confidence: 98%
See 1 more Smart Citation
“…It may be argued that in our way of analysis, we did not take into account some of the attractive properties of the MinResIV designs and the DSDs, especially that main effects can be estimated unbiased from 2‐factor interactions and for the DSDs also unbiased from quadratic effects. Also, it is well demonstrated, for instance Wolters and Bingham, that the “correct model” is not necessarily the one with the lowest MSE, but that it is normally among the ones with the lowest MSE. Hence, our reported success frequencies may, and especially for the MinResIV 12 and the DSD 12 designs, be a little pessimistic.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Other methods for variable selection that have been effective for these designs include Bayesian methods that use mixture prior distributions for the elements of β [41,26] and the application of stochastic optimisation algorithms [110].…”
Section: Variable Selection For Non-regular and Supersaturated Designsmentioning
confidence: 99%